Under-Age Children Returning From Jihadist Group Operation Areas: How Can We Make a Diagnosis and Construct a Narrative With a Fragmentary Anamnesis? - Klein, Anaelle; Mapelli, Alessandra; Veyret-Morau, Maurween; Levy-Bencheton, Julie; Giraud, François; di Chiara, Mercedes; Fumagalli, Marta; Lida-Pulik, Hélène; Moscoso, Ana; Payen de la Garanderie, Jérôme; Palazzi, Stephanie; Baleyte, Jean-Marc; et al. (Frontiers in Psychiatry, 2020)
Introduction Since 2011, the French government estimates that about 500 French children have been born in or taken by their parents to areas where terrorist operations prevail. Since May 2017, 75 children who returned to France have benefited from a dedicated health care system. Method This article is the result of clinical interviews conducted with 53 patients evaluated and taken care of at Avicenne Hospital in Bobigny. To our knowledge, no studies have been published on this subject. Results A total of 32 evaluations have been completed, all of which indicated the need for care for these children. Of these children, 64% are under 5 years old, and 59% were born in France. Their clinical profiles are heterogeneous and fluctuate with time. Discussion The multiple adverse events experienced by these children and the uniqueness of children born to families suspected by authorities of having participated in activities related to terrorism make this situation unprecedented. How can we make a diagnosis of PTSD without the help of a precise anamnesis? How can we help these children form a structuring narrative that avoids the pitfalls inherent to generalized fascination?